Come si costituisce un testimone? Edith Bruck testimone di vita a vita - Hanna Serkowska (Laboratoire Italien)
The article is dedicated to the work of Edith Bruck, in particular to La rondine sul termosifone, and refers to recent theories of the witness, of the ethical paradigm of the testimony, as well as of the forms of “life narratives”. The basic proposal is that the works under scrutiny show that there is a correspondence – apparent both from an ethical point of view and from the point of view of narrative structures and modes – between two types of testimony: because the person who is “submerged” (a victim of the Holocaust and/or unable to give a personal account because of their illness) needs someone else to narrate their life. In La rondine sul termosifone, E. Bruck, the author of numerous works in which she is the bearer of the memory for millions of Holocaust victims, becomes a witness on behalf of her husband Nelo Risi, suffering from a neurodegenerative disease. Thus, she expands the concept of testimony and redeems the figure of the witness, as claimed by Michal Givoni.